2011
DOI: 10.1186/1751-0147-53-24
|View full text |Cite
|
Sign up to set email alerts
|

Cattle brucellosis in traditional livestock husbandry practice in Southern and Eastern Ethiopia, and its zoonotic implication

Abstract: BackgroundCattle brucellosis has significant economic and zoonotic implication for the rural communities in Ethiopia in consequence of their traditional life styles, feeding habits and disease patterns. Hence, knowledge of brucellosis occurrence in traditional livestock husbandry practice has considerable importance in reducing the economic and public health impacts of the disease.MethodsA total of 1623 cattle sera were serially tested using the rose Bengal test as screening and complement fixation test as con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
70
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 11 publications
23
70
8
Order By: Relevance
“…Evidence suggests that when Brucella spp. is introduced into herds, a large proportion of animals will be infected and the infection will persist for a longer time [30][31][32]. Sharing of pasture and drinking water facilitate transmission of most infectious diseases, which is in line with the present findings of grazing as risk factor for Brucella and BVDV infections [33].…”
Section: Discussionsupporting
confidence: 53%
“…Evidence suggests that when Brucella spp. is introduced into herds, a large proportion of animals will be infected and the infection will persist for a longer time [30][31][32]. Sharing of pasture and drinking water facilitate transmission of most infectious diseases, which is in line with the present findings of grazing as risk factor for Brucella and BVDV infections [33].…”
Section: Discussionsupporting
confidence: 53%
“…At the same time, we believed that the reallocation of time and resources by the authorities to control other pandemics and re-emerging infections, notably the multiple outbreaks of FMD (Edwards, 2004;Wongsathapornchai et al, 2008), bird flu (H5N1) (Morris et al, 2005) and swine flu (H1N1) (Goodwin et al, 2011) led to asubstantial reduction in of nationwide brucellosis surveillance and control program. Previous studies have also reported that location, region or area have a significant correlation with brucellosis seropositivity, which, according to the authors, is attributable to management practices and other agroecological factors (Megersa et al, 2011). It is also possible that the difference was due to other confounding variables unaccounted for in this study.…”
Section: Discussionsupporting
confidence: 59%
“…Bovine brucellosis has recently been reported from different countries in Africa including Ethiopia, Zambia and Zimbabwe, indicating that the disease is present throughout the continent (Chimana et al 2010;Matope et al 2011;Megersa et al 2011;Tesfaye et al 2011). Bovine brucellosis was also reported from two of Nigeria's neighbour countries, Chad and Cameroon (Schelling et al 2003;Scolamacchia et al 2010;Bronsvoort et al 2009;Bayemi et al 2009).…”
Section: Introductionmentioning
confidence: 91%